Ανάπτυξη και αξιολόγηση ενός ενδυόμενου συστήματος ανίχνευσης κίνησης για κιναισθητικά καθήκοντα σε περιβάλλοντα εικονικής πραγματικότητας - Μουρελάτος, Ανδρέας (Εθνικό Μετσόβιο Πολυτεχνείο. Σχολή Μηχανολόγων Μηχανικών. Τομέας Βιομηχανικής Διοίκησης και Επιχειρησιακής Έρευνας, 2018)
Advances in computing, sensor and display technology mean that immersive virtual and augmented reality environments are becoming increasingly more realistic and affordable. Humans can now easily experience virtual environments (VEs) through visual means. However, in order to reap the full range of benefits these technologies can offer, it is of essence to provide the ability to control an avatar body within a VE and especially the upper limbs. The integration of arm movements in such environments both increases the immersion of the user, and opens new pathways for exploring and interacting with the VE. Moreover, it allows for increased capabilities in training and assisting humans in various tasks. Using three MPU9250 IMUs and an Arduino Nano microprocessor, we developed a wearable system for unobtrusively tracking the movement of the arm from the shoulder up to and including the palm. The system was used in conjunction with an Oculus Rift DK2 and an environment designed in the Unity Game Engine, to create a VE “shooting target practice” task. The above setting allowed a virtual arm to be completely controlled by the movements of the user’s arm in the real world with negligible lag. In this thesis a series of experiments will be presented, designed to determine whether the visibility of one’s limb movements in real time in a VE, improves the effectiveness in the execution of sensorimotor tasks within that environment. Extending from the above, we also explore the degree to which a human can assimilate a virtual representation of their arm with their body image, and subsequently incorporate this representation into their body schemas, as well as the speed and ease with which that assimilation occurs. The results of the experiments provide evidence on the effect of avatar arm visibility on the users’ performance and learning curve in the VE task. Visibility did not appear to have a significant effect on performance. Our assumption is that this is related to the nature of the experimental task. For this reason the experimental task was changed, allowing us to explore the diversification of the subjects’ strategy and results.